Rugby Health and Well-Being Study: protocol for a UK-wide survey with health data cross-validation - Roger Hawkes; Andrew Murray; Nigel K Arden; Nirmala Kanthi Panagodage Perera; Stephanie R Filbay; Steffan A Griffin; Maja R Radojčić; Lucy Gates (BMJ Open)
Introduction Rugby football (Union and League) provides physical activity (PA) with related physical and mental health benefits. However, as a collision sport, rugby research and media coverage predominantly focus on injuries in elite players while the overall impact on health and well-being remains unclear. This study aims to provide a greater understanding of the risks and benefits of rugby participation in a diverse sample of men and women, current and former rugby Union and League players from recreational to the elite level of play. We will explore: (1) joint-specific injuries and concussion; (2) joint pain and osteoarthritis (OA); (3) medical and mental health conditions; (4) PA and sedentary behaviour and (5) well-being (quality of life, flourishing and resilience).Methods and analysis The Rugby Health and Well-being Study is designed in two phases: (1) a UK-wide cross-sectional survey and (2) cross-validation using health register data from Scotland. Participants will be at least 16 years old, current or former rugby players who have played rugby for at least one season. We will report standardised, level of play-, sex- and age-stratified prevalence of joint injury, concussion, medical conditions and PA. We will describe injury/concussion prevention expectations and protective equipment use. Rugby-related factors associated with injury, pain, OA, PA, health and well-being will be explored in regression models. We will compare joint pain intensity and duration, elements of pain perception and well-being between recreational and elite players and further investigate these associations in regression models while controlling for confounding variables. In the second phase, we will validate self-reported with health register data, and provide further information on healthcare use.Ethics and dissemination The Yorkshire and the Humber—Leeds East Research Ethics Committee (REC reference: 19/HY/0377) has approved this study (IRAS project ID 269424). The results will be disseminated through scientific publications, conferences and social media.